A Community of Workers in Leonidas of Tarentum - Claire-Emmanuelle Nardone (Aitia, 2018)
The hellenistic epigrammatist Leonidas of Tarentum inherited the representation of workers which was shaped by archaic and classical greek culture and poetry, especially by Homer. This representation included clearly distinct and separated categories of workers and a specific status of the worker in the oikos and in society. However, as this epigrammatist reshapes literary traditions by representing humble characters as a class of individuals, he creates a new representation of a community of workers. This paper will focus on two aspects of this representation, which are distinct from their Homeric model but allow the epigrammatist to allude to it: the presence in Leonidas of allusions to networks of persons who practise the same profession and the fact these networks are part of a larger community of workers, which transcends traditional, professional and/or gender boundaries.